INTERDISCIPLINARY INTEGRATION IN IMPROVING THE COMPETENCES OF FUTURE ELEMENTARY EDUCATION TEACHERS TO EVALUATE THE QUALITY OF EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the importance of interdisciplinary integration in improving the competences of comprehensive evaluation of the quality of education for future primary education teachers, increasing their capabilities, is highlighted. It includes methods for teachers to study more deeply the complex factors that affect educational outcomes.